Microbiological and physical properties of pennywort (Centella asiatica) leaves using pulsed light technology - Rosli, Siti Zaharah; Mohd Adzahan, Noranizan; Radu, Son; Karim, Roselina; Yusof, N. L.; Koh, Pei Chen; Hambali, Nor Hasni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2020)
Pennywort (Centella asiatica) is a herbaceous vegetable commonly consumed raw as ‘ulam’ or salad. Consumption of raw leafy green vegetables is one of the pathogenic mechanisms that could cause foodborne outbreaks. The aim of the present work was therefore to investigate the effect of pulsed light (PL) treatment at fluences of 1.5, 4.2, 6.9, 9.6, and 12.3 J/cm² on the microbiological and physical quality of pennywort stored at 4 ± 1°C. Escherichia coli (E. coli) were inoculated onto the pennywort leaves before being exposed to PL and viewed using scanning electron microscopy (SEM). PL fluences of 6.9, 9.6, and 12.3 J/cm² significantly reduced the microbial count; however, the highest inactivation was obtained by using fluences of 9.6 and 12.3 J/cm². The color of pennywort was not significantly affected by PL treatment applied at lower fluences of 1.5, 4.2, and 6.9 J/cm²; however, at higher fluence, 9.6 and 12.3 J/cm², the color was affected. PL at 1.5, 4.2, 6.9, and 9.6 J/cm² was able to retain the texture appearance of the leaves. To conclude, PL at 6.9 J/cm² showed the best fluence to reduce total aerobic mesophilic count while retaining the physical properties of pennywort leaves and extend the shelf life to about four days. The inactivation of E. coli population was significantly higher at PL fluence of 6.9 J/cm². It was observed that PL caused the destruction to the surface of E. coli’s cell membrane. The reductions of samples inoculated with E. coli were better than those achieved in native microbiota. Furthermore, the present work also demonstrated that PL treatment was able to reduce the microbial count on pennywort leaves.